2021
DOI: 10.1155/2021/1344776
|View full text |Cite
|
Sign up to set email alerts
|

Introducing a Rheology Model for Non-Newtonian Drilling Fluids

Abstract: An API standard drilling fluid was investigated from laminar to turbulent flow conditions using an in-house-built viscometer at speeds from 200 to 1600 RPM. A power-based method was applied to obtain the apparent viscosity and the shear stress of the water-based drilling mud (WBM) in the annulus of the viscometer. Then, a MATLAB optimization program was developed to obtain model parameters for five rheology models integrated in a generalized Herschel-Bulkley-Extended (HBE) model and two widely used 4-parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The Rheological models estimation is crucial to feature drilling mud in dynamic conditions. The rheology models include Newtonian, Bingham plastic, Power law, Herschel-Bulkley, Sisko, Ellis, Casson, and Hyperbolic models [12,13]. The main objectives of the current work focus on formulation of smart water-based drilling fluids incorporated with green magnetite NPs and an industrial alkali waste (spent caustic) as pH controller.…”
Section: Introductionmentioning
confidence: 99%
“…The Rheological models estimation is crucial to feature drilling mud in dynamic conditions. The rheology models include Newtonian, Bingham plastic, Power law, Herschel-Bulkley, Sisko, Ellis, Casson, and Hyperbolic models [12,13]. The main objectives of the current work focus on formulation of smart water-based drilling fluids incorporated with green magnetite NPs and an industrial alkali waste (spent caustic) as pH controller.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have studied the effect of drilling fluid rheology on drill string vibration. Rashidi et al[10] developed the MATLAB optimization program, and used five classical rheological models and two four parameter models (Cross and Carreau models) extracted from Herschel Bulkley Extended (HBE) model to fit the experimental measured values. It is found that the Bingham, Cross, and HBE models have precisely matched the measurements in the viscometer and could be used to study the effect of drilling fluid rheology on drill string vibration.…”
mentioning
confidence: 99%